Reflections on low cost schools in Peru - Lazo Málaga, Oswaldo (2020)
The privatization of education in Peru has brought with it the proliferation of low cost private schools. In our country, these types of schools are characterized by their low educational quality and their high segregation rate. In the present work, we propose a set of recommendations necessary to be implemented to improve the regulation and supervision of the low-cost educational service in Peru.